444 PULSE WAVE VELOCITY TO GLOBAL WORK EFFICIENCY RATIO IN HYPERTENSION: A NEW WAY TO EXPLORE VENTRICULAR-ARTERIAL COUPLING. (15th December 2022) - Trimarchi, Giancarlo; Lofrumento, Francesca; Mandraffino, Giuseppe; Cusmà-piccione, Maurizio; Spanò, Federico; Certo, Giuseppe; Manganaro, Roberta; Carerj, Scipione; Di Bella, Gianluca; Zito, Concetta
Abstract: Introduction: Ventricular–arterial coupling (VAC) is considered as the cornerstone of the functional interaction between ventricles and the arterial system. VAC is commonly assessed as arterial elastance (Ea) to ventricular end-systolic elastance (Ees) ratio and it has independent prognostic value in hypertension, so it may be used to refine risk stratification and monitor therapeutic interventions in hypertensive patients. Therefore, VAC may be better characterized by the measurement of each component of this ratio through novel and more sensitive markers of myocardial function (e.g. global longitudinal strain and myocardial work parameters) and arterial function (e.g. pulse wave velocity). In this context, we aim to investigate whether new coupling indices may be able to identify left ventricular (LV) performance changes induced by blood pressure (BP) overload earlier than conventional ones. Methods: 50 young individuals were prospectively enrolled, distinguishing between newly diagnosed untreated hypertensives (n= 25; 40±8 years) and controls (n=25; 39±9 years), matched for age and gender. All patients underwent at the same time carotid-femoral pulse wave velocity (PWV) measurement through an applanation tonometer (SphygmoCor® XCEL) and a transthoracic echocardiogram to calculate Ea/Ees ratio, assessed as end-systolic volume to stroke volume ratio (ESV/SV), global longitudinal strain (GLS) and myocardial work efficiency (GWE). Two new indices of VAC were derived: PWV/GLS, previously validated and PWV/GWE, still unknown. Results: Ea/Ees ratio was lower in hypertensives (0, 48±0, 17) than in controls (0, 57±0, 14) but without any signiﬁcant difference (p=0.18), whereas PWV/GLS was signiﬁcantly higher in hypertensives than in controls (0, 45±0, 19 vs 0, 35 ± 0, 09 m/sec%; p= 0, 02). PWV/GLS ratio correlated to Ea/Ees (r= 0, 52; p < 0, 01), diastolic dysfunction degree (r=-0, 59; p<0, 001), age (r=-0, 64; p<0, 001), systolic BP (r=-0, 41; p=0, 002), diastolic BP (r=-0, 39; p=0, 005) and mean arterial pressure (MAP) (r=-0, 40; p=0, 004). PWV/GWE was higher in hypertensives than in controls (0, 10± 0, 02 vs 0, 08±0, 01 m/sec%; p=0, 001) and it was associated with Ea/Ees (r=- 0, 55; p = 0, 006), age (r= 0, 59; p<0, 001), diastolic dysfunction degree (r=0, 55;p< 0, 001), systolic BP (r=0, 8; p< 0, 001), diastolic BP (r=0, 5;p< 0, 001) and MAP (r=0, 52; p<0, 001). Conclusions: Innovative indices of ventricular-arterial coupling could be more sensitive to investigate the impact of hypertension on LV performance.